Industrialização e desenvolvimento do sudoeste do Paraná - Flores, Edson Luiz (2009)
How wrote Marx and Engels (1998), the production is very important to man, more than this, it`s the responsible by own humanization; to measure that the men, to opposite of the animals that live by nature (offer of foods, resisting by climatic intemperance etc), get to produce the instrument of survival (foods, clothes, home etc). However, we verified that in the human sciences, specifically at the Geography, in the last epochs has been given little attention to the production, mainly to industrialization. In this study, we realized a analysis about the industry`s importance at the Southwest of the Parana`s development, region of new population occupation, happened mainly after the 1940`s. By the realization of that study, proceeded to light from the historic materialism, method which to consist, thick manner, in to analyses the formations and transformations occurred at the society from active production and from work`s connections intrinsic to its. The theoretical reference Marxism mainly the Karl Marx, Friedrich Engels, Vladimir Lenin, Karl Kautsky, Ignácio Rangel, Armem Mamigonian`s studies, among others abetted us to that realized a detailed research, interviewing owns and executives of industrial unities from region, salaried workers etc, looking at to get information and dies about the thematic studied. In this discourse, we analyzed: 1) the importance of the industry (mainly the wood`s branch) to the population of this region from Parana; 2) we verified the conditions that the social formation (marked by presence of few owns of earth, craftsmen and merchants) offered to organize a few merchant production; 3) we saw the importance that had the financial capital, as modernizing the agricultural as financing the industrial production (mainly from the second half at 1970`s); 4) we saw the importance that the abetment politics to industrialization, the offer of raw materials, and of work`s power, have been to attract industrial unities to this region; and, 5) we verified the increase of income advanced by industry, that besides, has been contributed, somehow, to a geral advancement of the life`s conditions from Southwest of the Parana`s population.